Islamic Business Ethics-Based Digital Marketing to Increase Sales: A Study of MSMEs in Indonesia in 2022–2024 - Nur Komariyah; Mashudi Mashudi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research study aims to implement digital marketing for MSMEs in Indonesia that aligns with the principles of Islamic business ethics while providing strategic recommendations to ensure digital marketing adheres to Sharia principles in Islamic business ethics. The novelty of this research lies in the integration of digital marketing with the principles of Islamic business ethics in the context of Indonesian MSMEs in the 2022-2024 period, a topic that has not been comprehensively studied nationally and in that period. The study employed a qualitative phenomenological approach involving 15 purposively selected informants. Data were collected through semi-structured interviews, digital documentation, and secondary sources from the Indonesian Chamber of Commerce and Industry (KADIN). Data analysis was conducted using the Colaizzi thematic technique to comprehensively explore the meaning of informants' experiences. The results show that the implementation of Sharia-compliant digital marketing is reflected in honest information, price transparency, and polite communication, which in turn builds consumer trust and positively impacts sales growth. This research confirms that Islamic ethics not only serves as a moral guideline but also has strategic value in strengthening the reputation and sustainability of MSME businesses in the digital era.